On the Edge of Escalation: How US Development Policy Deals with the Political Economy of War in Mindanao - Pospisil, Jan (Kasarinlan: Philippine Journal of Third World Studies; Vol 20 No 2 (2005): International Political Economy, 2007)
Development policy is one of the most important instruments used by the core states of the world system in pursuit of national interest. This article examines the development cooperation between the governments of the United States and the Philippines in the conflict-affected regions of Mindanao. Although the present United States Agency for International Development (USAID) programs in Mindanao started in 1997, it is barely possible to make out sustainable positive effects in the sense of a potential disintegration of the war system. Consequently, such international political-economic intervention is considered risky, because its long-term results are not predictable in a systemic context.
Keywords: conflict economy; development policy; Mindanao; USAID; war systems; world system analysis